Analisis Break Event Point (BEP) Sebagai Alat Perencanan Laba Jangka Pendek Pada UMKM Cafe Limas Palembang - Sinta Agustiani Putri; Eka Jumarni Fithri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This final report is made to help performing profit planning with fixed costs and variable costs as a basis in doing profit planning using Break Even Point (BEP). The title of this final report is